Cold/hot pad differentiating assay of property differences of Mahuang and Maxingshigan decoctions. (2nd July 2016) - Zhao, Yanling; Jia, Lei; Wang, Jiabo; Zou, Wenjun; Yang, Hongbo; Xiao, Xiaohe
Abstract: Context : Chinese medicines with different cold/hot properties have various pharmacological actions on multiple organisms. Objective : The objective of this study was to explore the cold/hot property differences of traditional Chinese medicine formulas of Mahuang and Maxingshigan decoctions. Materials and methods : A novel cold/hot pad differentiating assay method based on the Intelligent Animal Temperature Tropism Behavior monitoring system at 20 °C (cold pad) and 30 °C (hot pad) was introduced to investigate the variability of temperature tropism among the mice treated by 0.4 mL/20 g (drug volume/body weight) of Mahuang decoction and Maxingshigan decoction, respectively. Meanwhile, the oxygen consumption and activities of adenosine triphosphatase (ATPase) were measured to explore the energy metabolism mechanism. Results : Results showed that the differences between cold/hot properties of Mahuang decoction and Maxingshigan decoction were significant ( p < 0.05). Mahuang decoction produced significant synergic effect (a combination index of 1.60), while Maxingshigan decoction expressed significant antagonistic effect (a combination index of 0.35). The changes of energy metabolism including ATPase activity and oxygen consumption might be the possible factors to result in the differences. Those influences tended to be coherent with the definition of cold/hot properties of Chinese medicines based on traditional Chinese medicinal theory. Conclusions : The results indicated that the method based on cold/hot pad differentiating array could objectively and quantitatively represent the cold/hot properties of different compatibilities of traditional Chinese medicines in an ethological way according to the changes of animal's temperature tropism. These findings would provide some experimental basis and data references as well as a novel evaluation method for the study of the regularity of recipe composition.